Mathematical Communication and Social Skills of The Students through Pair Check Type Cooperative Learning Models - Farokah, Esti; Winarso, Widodo (SUKMA: Jurnal Pendidikan, 2021)
Lack of students 'social skills makes students' mathematics learning less optimal. The learning model that is carried out is often not maximizing the learning process-oriented towards mathematical communication skills. This makes the teacher strive for a learning method or strategy to foster students' social skills and mathematical communication skills. The Pair Check method is one of the learning methods expected to train and improve students' social skills and mathematical communication skills. The subjects of this study were 24 students of class VII B MTs Riyadlul Ulum Bendungan. The results showed that: (1) students social skills had a percentage of 74.05% with the "most" criteria, which means that most of the students had quite good social skills. At the same time, students' mathematical communication skills have a percentage of 49.55% in the less category. (2) the application of the pair check method can improve students' social skills and mathematical communication. This can be seen from the post-tests average value, which is greater than the pretest, namely pretest < posttest or 13.88 < 19.58. (3) the application of the pair check method has implications for the social skills and mathematical communication skills of students at MTs Riyadlul Ulum Bendungan. This can be seen from the results of the questionnaire and the test results after the pair check method was applied. It was better than the questionnaire results, and the test results before the pair check method were applied